Frosted Branch Angiitis Associated With Cytomegalovirus in a Pediatric Autologous Stem Cell Transplant Patient: Case Report and Review of the Literature. Issue 2 (March 2022) - Kacar, Marija; Cacciotti, Chantel; Shen, Carl; Fulford, Martha; Lysecki, Dave; Fleming, Adam
Abstract : Background: Frosted branch angiitis (FBA) is a rare phenomenon of panuveitis which may occur secondary to cytomegalovirus (CMV) causing acute visual disturbances. CMV infection is a known complication in allogenic stem cell transplant (SCT) patients but is uncommon following autologous SCT. Observation: We describe a 17-month-old medulloblastoma patient with sudden onset visual impairment following second autologous SCT. The patient was CMV seropositive, polymerase chain reaction negative before second SCT. At the time of presentation with visual complaints, the patient was diagnosed with FBA associated with CMV reactivation. Treatment included antivirals and immunosuppressive medication with visual recovery. Conclusion: FBA induced by CMV should be considered as a differential diagnosis in pediatric patients undergoing autologous bone marrow transplant with rapidly progressive visual impairment.